Subcutaneous Emphysema, Pneumomediastinum and Spinal Epidural Emphysema As Complications of Violent Coughing: A Case Report: Spontaneous pneumomediastinum - Yılmaz, Fevzi; Zortuk, Ökkeş (Acta Biomedica Atenei Parmensis, 2021)
Spontaneous pneumomediastinum (SPM) is a rare condition characterized by chest pain of sudden onset, difficulty breathing, dysphagia, dysphonia, and subcutaneous emphysema, which are some-times accompanied by pain in the neck or back. This condition typically has a benign character that limits itself, and supportive therapy is all that is needed; however, life-threatening consequences may occur, such as upper respiratory tract obstruction, esophageal injury, and tracheal damage, requiring surgery. We report here a man aged 19 years who coughed vigorously due to acute allergic asthma, which lead to subcutaneous emphysema starting from the neck down to the chest, mediastinum and spinal epidural space. This case report stresses the importance of including SPM in the differential diagnosis of cough and chest pain in the young.